The View Of Efl Learners On Using Movie Subtitle In Teaching Reading Comprehension - Bahri, Syamsul; Permatasari, Dea Utami (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the advantages of teaching reading comprehension by using movie subtitle. The aim of this study is to investigate the good points of movie subtitle in improving students’ reading comprehension. The results from test and questionnaire show that this technique support teaching reading. This can be proved that students’ result was sharply improved. It means that the increase from the pre-test and the post-test was 60 %. The findings from the analysis of questionnaire show most of the students provide positive responses about students’ reflection on learning by using this technique in which the fast majority (69 %) of them agreed that movie subtitle technique helps them in comprehending the reading and also get a new knowledge from it. Therefore, it can be concluded that movie subtitle provide strong effect on students’ reading score and positive influence for them